Granulocyte-Macrophage Colony-Stimulating Factor Regulates Effector Differentiation of Invariant Natural Killer T Cells during Thymic Ontogeny - Bezbradica, J; Gordy, L; Stanic, A; Dragovic, S; Hill, T; Hawiger, J; Unutmaz, D; Van Kaer, L; Joyce, S (Cell Press, 2006)
Invariant natural killer T (iNKT) cell-derived cytokines have important functions in inflammation, host defense, and immunoregulation. Yet, when and how iNKT cells undergo effector differentiation, which endows them with the capacity to rapidly secrete cytokines upon activation, remains unknown. We discovered that granulocyte-macrophage colony-stimulating factor (Csf-2)-deficient mice developed iNKT cells that failed to respond to the model antigen α-galactosylceramide because of an intrinsic defect in the fusion of secretory vesicles with the plasma membrane. Exogenous Csf-2 corrected the functional defect only when supplied during the development of thymic, but not mature, splenic Csf-2-deficient iNKT cells. Thus, we ascribe a unique function to Csf-2, which regulates iNKT cell effector differentiation during development by a mechanism that renders them competent for cytokine secretion.